2019
DOI: 10.1111/cen.13934
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the role of anti‐Mullerian hormone and LH/FSH ratio in diagnosis of polycystic ovary syndrome

Abstract: Objective: This study explores the role of anti-Mullerian hormone (AMH) and LH/ FSH ratio in diagnosis of polycystic ovary syndrome (PCOS). Methods: In this multicentre cross-sectional descriptive study, a total of 863 infertile women between 18 and 45 years were evaluated at three infertility centres in Vietnam and were recruited from June 2016 to June 2017. The patients were classified into two groups: Group I included 441 patients with PCOS (based on Rotterdam criteria consensus) and Group II included 422 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…PCOS represents a chronic endocrine-metabolic disease with hyperandrogen and low estrogen (53). The LH/FSH ratio was regarded as a main biomarker of diagnosis in PCOS (54,55). The notably increased T level is usually considered as a marker of hyperandrogenism in PCOS (56).…”
Section: Discussionmentioning
confidence: 99%
“…PCOS represents a chronic endocrine-metabolic disease with hyperandrogen and low estrogen (53). The LH/FSH ratio was regarded as a main biomarker of diagnosis in PCOS (54,55). The notably increased T level is usually considered as a marker of hyperandrogenism in PCOS (56).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hormone profile was observed to have highly significant differences in LH, prolactin, and estradiol levels and insignificant differences in FSH and progesterone between PCOS patients and control groups. The studies showed that the LH/FSH ratio is 2-3-fold different between groups (20,21). In this study, the ratio of LH/FSH in PCOS women was 5:1 for study patients 15-29 years and 4:1 for 30-45 years compared with healthy women ratios in which an elevated LH/FSH ratio could disrupt ovulation.…”
Section: Discussionmentioning
confidence: 46%
“…This would help in the identification of PCOS patients from normal women. A recent case-control study (441 PCOS women and 422 non-PCOS women) was conducted to examine the diagnostic ability of the LH/FSH ratio in the identification of PCOS cases (39). An optimum LH/FSH ratio cut-off value of 1.33 was significant to diagnose PCOS (area under curve = 0.867).…”
Section: Discussionmentioning
confidence: 99%